The Effect of Calisthenics Exercises on Body Composition in Soccer Players - Cigerci, Ali Erdem; Genç, Harun (Progress in Nutrition, 2020)
Study Objectives: The purpose of the study was to examine the effect of calisthenics exercises on body composition in soccer players.Methods:18 male soccer players with ages of 18,16+1,04 years, height 174,94+7,68 m, body weight 69,99+8,68 kg participated in the study voluntarily. The soccer players participating in the study were randomly divided into 2 groups. 9 soccer players in the calisthenics exercises group (CEG) performed calisthenics exercise and soccer training, and 9 soccer players in the control group (CG) performed only soccer training. The study lasted a total of 8 weeks, with 3 workouts per week. Analysis of intergroup, intragroup, and the effect of training were carried out with repeated measures ANOVA. Significance was set at 0.05. Results: While there was no difference in the BMR and TBW of the subjects, there was a difference in pre and post-test measurements of body composition such as BW, BMI, FP, FM, and FFM. In comparison of pre and post-test changes of upper extremities between groups, there was a significant difference in the all variables of the subjects in pre and post-test measurements of RAFP, RAFM, RAFFM, LAFP, LAFM, and LAFFM in terms of inter-group, intra-group, and group*test interaction. In comparison of pre and post-test changes of lower extremities between groups, there was no difference in the RLFP of the subjects; there was a significant difference pre and post-test measurements of body composition such as RLFM, RLFFM, LLFP, LLFM,and LLFFM. Conclusion: It can be said that an 8-week calisthenics exercise can provide positive development of the whole body composition of soccer players.